The development of a small and medium-sized business risk management intervention tool - Niël Almero Krüger; Natanya Meyer (Journal of Risk and Financial Management, 2021)
Risk is inevitable in business. For large companies, risk management is formalised and structured through compliance with industry standards. However, small and medium-sized businesses (SMEs) rarely have adequate resources to develop their own standards or conform to pre-established criteria. This results in an increased vulnerability to risk, which tends to undermine SMEs' sustainability. The primary reasons for the low adoption rate of risk management are related to the tremendous initial difficulty in orientating the business concerning risk and the significant investment of the workforce in developing and implementing a structured managerial process. The objective of this paper is to produce a guided process tool for small and medium-sized businesses with which they can identify, evaluate, and appropriately address risks from an SME perspective. Moreover, this intervention would offer enhancements at no cost beyond the time of its implementation. In order to identify what constitutes holistic risk management, document analysis was applied, which utilised risk management standards, academic articles, books, and regulatory policy and strategy documentation. The identified elements were integrated with a tool that improves business owners' capacity to position themselves in context with their daily risk management challenges.
Keywords: 330; quantitative; risk; risk intervention; risk management; risk standard; small businesses; SME; sustainability; tool